Light neutral-meson production in pp collisions at √s = 13 TeV - Acharya, S.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Akishina, V.; et al. (Springer Science and Business Media Deutschland GmbH, 2025)
The momentum-differential invariant cross sections of π⁰ and η mesons are reported for pp collisions at √s = 13TeV at midrapidity (|y| < 0.8). The measurement is performed in a broad transverse-momentum range of 0.2 < Pᴛ < 200 GeV/c and 0.4 < Pᴛ < 60 GeV/c for the π⁰ and η, respectively, extending the Pᴛ coverage of previous measurements. Transverse-mass-scaling violation of up to 60% at low transverse momentum has been observed, agreeing with measurements at lower collision energies. Transverse Bjorken x (xₜ) scaling of the π⁰ cross sections at LHC energies is fulfilled with a power-law exponent of n = 5.01±0.05, consistent with values obtained for charged pions at similar collision energies. The data are compared to predictions from next-to-leading order perturbative QCD calculations, where the π⁰ spectrum is best described using the CT18 parton distribution function and the NNFF1.0 or BDSS fragmentation function. Expectations from PYTHIA8 and EPOS LHC overestimate the spectrum for the π⁰ and are not able to describe the shape and magnitude of the η spectrum. The charged-particle multiplicity dependent π⁰ and η Pᴛ spectra show the expected change of the spectral shape, characterized by a flatter slope with increasing multiplicity. This is demonstrated across a broad transverse-momentum range and up to events with a charged-particle multiplicity exceeding five times the mean value in mínimum bias collisions. The η/π⁰ ratio depends on the charged-particle multiplicity for Pᴛ < 4 GeV/c. PYTHIA8 and EPOS LHC qualitatively explain this behavior with an increasing contribution from the feed-down of heavier particles to the π⁰ spectrum.
Keywords: Hadron-Hadron Scattering, Particle and Resonance Production, QCD; https://purl.org/pe-repo/ocde/ford#1.03.03